Radiative Effect of Dissipation Function in the Development of Temperature Profiles in a Pipe with Isothermal Convection - Bello, F.A.J.; Mustapha, L.O. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2015)
Temperature profiles in a fluid flow inside a porous vertical channel influenced by the presence of variablethermal conductivity and dissipation function are important features in the study of magneto hydro dynamics.In this study, the effects of temperature and variable fluid properties on unsteady hydro magnetic flow of aradiating gas inside a porous were investigated. The coupled nonlinear partial differential equations derivedfrom the governing equations of the fluid were solved by the method of successive approximation techniques. Itwas found that the dissipation function was completely neglected at the centre line but maximum at the wall ofthe channel where a fully developed temperature profiles reached its peak. The heat flow balances at the walldue to high temperature and dissipation function